Capital gains taxation and funding for start-ups - Edwards, Alexander; Todtenhaupt, Maximilian (Journal of Financial Economics, 2020)
We examine how capital gains taxes affect investment in private start-up (i.e., pre-IPO) firms. Using data on capital raised in individual funding rounds, we estimate the effect of the 2010 SBJA, which implemented a full exemption from federal capital gains tax on the sale of qualified shares. Because of the resulting higher expected after-tax returns, we hypothesize and find evidence consistent with this capital gains tax reduction increasing the amount of investment in start-up firms per funding round by about 12%. The effect is stronger in start-up firms that are likely to have greater administrative capacity. We estimate that about one-third of the tax benefit is captured by investors.